2010
DOI: 10.3346/jkms.2010.25.6.912
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Clinical Characteristics and Phenotypes between Prepubertal- and Adolescent-Onset Bipolar Disorders

Abstract: The aim of this study is to describe the clinical characteristics of prepubertal- and adolescent-onset bipolar disorder (BD) and to identify any clinical differences between patients with prepubertal- and adolescent-onset BD. We analyzed the clinical records of 53 inpatients with BD. These patients were divided into prepubertal-onset and adolescent-onset groups. We also divided the subjects into narrow, intermediate, and broad phenotypes according to the definitions proposed by Leibenluft and colleagues. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…1 , nine studies met eligibility criteria for inclusion in the review. The CASP assessment revealed that three studies achieved good-to-high-quality ratings (Findling et al 2001 ; Birmaher et al 2009 ; Chan et al 2011 ), three were rated as good-to-modest (McElroy et al 1997 ; Lazaro et al 2007 ; Safer et al 2012 ), whilst three studies achieved lower scores, suggesting some methodological weaknesses (Ballenger et al 1982 ; Jerrell and Shugart 2004 ; Song et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 , nine studies met eligibility criteria for inclusion in the review. The CASP assessment revealed that three studies achieved good-to-high-quality ratings (Findling et al 2001 ; Birmaher et al 2009 ; Chan et al 2011 ), three were rated as good-to-modest (McElroy et al 1997 ; Lazaro et al 2007 ; Safer et al 2012 ), whilst three studies achieved lower scores, suggesting some methodological weaknesses (Ballenger et al 1982 ; Jerrell and Shugart 2004 ; Song et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-six percent of the studies (5 out of 9) compared the symptoms of (hypo)mania in children versus adolescents (Findling et al 2001 ; Lazaro et al 2007 ; Birmaher et al 2009 ; Song et al 2010 ; Chan et al 2011 ). Two studies combined children and adolescents into one group (minimum age 7 years; maximum age 17 years) and compared the younger group with adults (Jerrell and Shugart 2004 ; Safer et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 In particular, diagnosis is challenging in pre-pubertal and adolescent patients, as their symptoms may not meet the DSM-IV criteria. 3 Also, studies suggest that even during the euthymic state of BD, cognitive and functional abnormalities can persist. 4 Thus, biomarkers for BD would be very useful in early diagnosis, disease control, measuring treatment response, and developing new therapeutic methods.…”
Section: Introductionmentioning
confidence: 99%